Ten-year profile of acute poisoning patients presenting to an Accident and Emergency Department requiring intensive care in a regional hospital of Hong Kong. Issue 1 (January 2019) - Ng, Fu
Background: Hong Kong Poison Information Centre publishes annual reports on all poisoning cases received by the Centre in that year since 2006. However, there is little data about acute poisoning cases requiring intensive care unit admissions in Hong Kong. Objective: To report and analyze the 10-year poisoning data of acute poisoning patients presenting to an Accident and Emergency Department requiring intensive care in a regional hospital of Hong Kong. Methods: This was a retrospective study on patients presented from January 2007 to December 2016. These cases were retrieved from Clinical Data Analysis and Reporting System of the Hospital Authority, Hong Kong. Clinical data of these cases were then retrieved from patients' electronic records. Results: A total of 270 cases were analyzed during the period. There were 152 (56.3%) male patients and 118 (43.7%) female patients. The middle aged group (age 30–39 and age 40–49) constitutes nearly half (48.6%) of all these admissions. Around 50% of them had history of psychiatric illness. Nearly 40% of them were known substance abusers. Majority of the patients (66.7%) were admitted directly from Accident and Emergency Department. The commonest cause was suspected self-harm (56.3%). When ethanol (13%) was excluded, the five commonest types of poisons were benzodiazepine (26.3%), opioids (20.7%), zopiclone (18.5%), carbon monoxide poisoning (13%), and household products (10.7%). Twenty-seven patients (10%) had decontamination done in Accident and Emergency Department or Emergency Medicine Ward. 112 patients (41.5%) were given one or more antidotes in Accident and Emergency Department and Emergency Medicine Ward. Altered mental status was the most frequently found complications (72.2%) in these patients. 76 patients (28.1%) required endotracheal intubation in Accident and Emergency Department. The length of stay in Intensive Care Unit ranged from 1 to 7 days with an average of 2.1 days. There were 25 deaths (9.3%) and 31 patients with major effects (11.5%). Conclusion: An estimate of 9.4% of acute poisoning patients presenting to Accident and Emergency Department might need Intensive Care Unit care at certain stage of their hospital stay. Benzodiazepine, opioids, zopiclone, carbon monoxide poisoning, and ethanol were the top five poisons in our series from 2007 to 2016. The mortality rate (9.3%) was high in our series given that there were more substance abusers.